The unifying effect of music in a community: a case study of the Lady Grey Passion Play - Davel, Irma (University of the Free State, 2020)
Conflict has detrimental effects on the dynamics in a community. The purpose of this research is to investigate to which extent music as an integrated part of a community project can contribute as a unifying factor in the community. The research included an investigation of the level of social transformation that may be possible through hosting a community project and utilised Brown’s model of social enhancement. Other important matters of interest were how the music of a community project such as the Lady Grey Passion Play serves as an emotive reward enhancer, as well as a helpful tool for persuasion and manipulation. Community projects have the possibility to accommodate change regarding mutual respect, reciprocity, group forming, cohesiveness and creating positive energy. Fourteen participants, selected by means of purposive sampling because of their specific knowledge and lived experiences of the Lady Grey Passion Play, were interviewed using open-ended, non-leading questions. The data was analysed using inductive analysis. It allowed me to build and decode its subjective reality and create meaning within the social context of the Passion Play. The main findings of the study can be summarised as follows: Through the annual presentation of a community event with integrated music, unity can be nurtured, boundaries may subside with resulting higher levels of tolerance, and conflict between the members of different communities may decrease. The practical implications of this study’s findings are that beliefs, ideologies and attitudes may lead to persuasion and manipulation through music. Music has an impact on mood and behaviour, and people become inspired by listening to it. There is, therefore, a possibility that unity can be promoted in a community through the use of music in a recurring community event.
Keywords: Thesis (Ph.D. (Odeion School of Music))--University of the Free State, 2020; Passion Play; Music as unifying component; Community transformation; Group cohesion; Community projects; Music - Social aspects; Lady Grey (South Africa); Social enhancement - Brown's model